Pancreatic surgery in elderly patients: results of 329 consecutive patients during 10 years - Bozkurt, Emre; Özoran, Emre; Özata, İbrahim Halil; Bilgiç, Çağrı; Kaya, Mesut; Tüfekçi, Tutku; Tellioğlu, Gürkan; Bilge, Orhan (Frontiers in Medicine, 2023)
Introduction There is a progressive shift from a younger population to an older population throughout the world. With the population age shift, surgeons will be more encountered with older patient profiles. We aim to determine age-related risk factors of pancreatic cancer surgery and the effect of patient age on outcomes after pancreatic surgery. Materials and methods A retrospective review was conducted with data obtained from consecutive 329 patients whose pancreatic surgery was performed by a single senior surgeon between January 2011 and December 2020. Patients were divided into three groups based on age: patients younger than 65 years old, between 65 and 74 years old, and older than 74 years old. Demographics and postoperative outcomes of the patients were evaluated and compared between these age groups. Results The distribution of a total of 329 patients into the groups was 168 patients (51.06%) in Group 1 (age <65 years old), 93 patients (28.26%) in Group 2 (age ≥65 and <75 years old), and 68 patients (20.66%) in Group 3 (age ≥75 years old). The overall postoperative complications were statistically significantly higher in Group 3 than in Group 1 and Group 2 (p = 0.013). The comprehensive complication index of the patients in each group was 23.1 ± 6.8, 20.4 ± 8.1, and 20.5 + 6.9, respectively (p = 0.33). Fisher’s exact test indicated a significant difference in morbidity in patients with ASA 3–4 (p = 0.023). In-hospital or 90-day mortality was observed in two patients (0.62%), one from Group 2 and one from Group 3. The 3-year survival rates for each group were 65.4%, 58.8%, and 56.8%, respectively (p = 0.038). Conclusion Our data demonstrate that comorbidity, ASA score, and the possibility of achieving a curative resection do have significantly more impact than age alone.